Analisis Penanganan Surat Masuk dan Keluar pada Biro Kesejahteraan Rakyat Sekretariat Daerah Provinsi Sumatera Utara - Hanny Rahmadani Ritonga (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Managing archives of incoming and outgoing letters is an important activity that must be carried out by an agency. Correspondence activities must receive serious attention, because the contents of letters to agencies will be a means of achieving the agency's goals, therefore there is a need for good mail management in a company or agency. This research aims to analyze the role of the regional secretariat in managing incoming and outgoing mail at the North Sumatra Governor's Office, to find out what obstacles are found in managing incoming and outgoing mail. This research is descriptive qualitative research and data collection techniques through direct observation, interviews and documentation regarding procedures for managing letters. Based on the research results, it shows that mail management at the North Sumatra Governor's Office includes 1) receiving letters, 2) recording letters, 3) processing letters, 4) directing letters, and finally 5) distributing letter. The results of the research show that the management of incoming and outgoing mail at the People's Welfare Bureau of the Regional Secretariat of North Sumatra Province has not been running effectively and efficiently, where the management of outgoing mail has not been running as it should, which is due to unsupportive facilities and infrastructure.